Influence of welding on high strength steel butt joints - Chen, Cheng (2019)
High strength steel (HSS) attracts attention of researchers for its high strength to weight ratio. Since it is easier to achieve uniform material properties during manufacturing, HSS is mainly available in the plate form. As a result, HSS plates are often welded to form built-up sections for constructional usage. Generally, severe temperature change is induced around the weld area during welding process, and it directly leads to microstructure transformation in the heat-affected zone (HAZ) and mechanical property changes of welded HSS joints. In this study, the influence of welding on high strength steel (HSS) butt joints is investigated experimentally and numerically. In order to achieve the intended investigation purposes, the whole study is divided into four parts, including material property study of HSS after cooling from different peak temperatures with different cooling rates, experimental study of welding influence on HSS butt joints, numerical simulation of welding influence and its corresponding verification, and numerical parametric study of cooling rate on tensile behaviour of HSS butt joints. Based on the experimental and numerical results, conclusions can be obtained that the mechanical property of HSS is affected by both peak temperature and cooling rate. After welding, the tempered martensite of base material is transformed to granular bainite in the coarse-grained HAZ, and to ferrite and cementite in the fine-grained HAZ. In tempering zone of HAZ, some of the tempered martensite decomposes to ferrite. The microstructure transformation in HAZ results in hardness variation and directly leads to mechanical behaviour change of HSS butt joints. Furthermore, the proposed simulation method is proved to be reasonable and accurate to predict the mechanical behaviour of HSS butt joints after welding, and the subsequent parametric study reveals that cooling rate control can improve the post-weld strength of joint to satisfy the design requirements.